Interleukin 18 as an early marker or prognostic factor in acute pancreatitis - Janiak, Adam; Leśniowski, Bartosz; Jasińska, Anna; Pietruczuk, Mirosława; Małecka-Panas, Ewa (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : Acute pancreatits (AP) still reqiures better diagnostic and therapeutic options to be introduced in order to decrease its morbidity and mortality. It appears that the assessment of serum levels of interleukin-18 (IL-18) and its correlation with C-reactive protein (CRP) may provide adequate prognostic value. Aim : To measure serum concentrations of IL-18 and inflammation markers such as CRP in patients with AP during subsequent hospital stay days and to assess the role of IL-18 as an early AP marker and prognostic factor. Material and methods : Thirty-two patients aged 47 ±16.7 years were included into the study (17 males and 15 females), in whom AP was diagnosed based on ultrasound and computer aided tomography imaging and amylase. Serum amylase, CRP, and IL-18 levels were measured on the 1 st , 2 nd , 3 rd , and 5 th days of hospital stay. All patients were scored “B” according to Balthazar and mild AP based on Ranson criteria. The control group consisted of 30 healthy volunteers aged 50.7 ±12.4 years (15 males and 15 females). Results : The average IL-18 serum level in the control group was 86.91 ±4.94 pg/ml. Mean IL-18 study group levels were 128.4 ±7.6 pg/ml on the 1 st , 112.0 ±4.4 pg/ml on the 3rd, and 122.8 ±6.8 pg/ml on the 5th day of AP, and were significantly higher than those in the control group, accordingly: p < 0.001, p < 0.005, p < 0.001. A positive correlation between IL-18 and CRP serum concentrations was observed. A slight increase in correlation was observed as the days went by. Conclusions : We concluded that the serum IL-18 level increases in the initial phase of AP , and it may be used as an inflammatory reaction marker in patients with AP, and it is correlated with CRP, which may indicate its prognostic role in AP.